Substrates in Morinda citrifolia staces rooting - Paixão, Marcus Vinicius Sandoval (2017)
The noni (Morinda citrifolia L.) belongs to the Rubiaceae family, growing extensively among the Pacific islands, being considered one of the most significant traditional medicine plants of these communities. Its introduction occurred only a few years ago, and because of this, there is still not enough propagating material for cultivation on a commercial scale, but in the last decades there has been a significant increase in commercial interest in relation to the products containing this plant, mainly the juice of noni fruits. The objective of this study was to evaluate different substrates in the rooting of noni cuttings. The experiment was conducted at the seedling nursery at the Federal Institute of Espírito Santo. Beech cuttings were harvested in 20 cm long noni adult plants and placed in 290 mL tubing on substrates: soil, sand, bioplant® and vermiculite. The design was completely randomized, with five replications of twelve stakes, being evaluated after 120 days the variables: survival of the stakes; number of leaves; collecting diameter; root length; volume of roots; root green mass; green leaves; dry mass root and dry mass leaves. The soil substrate showed to be superior to the other substrates, being recommended the early transplant of noni cuttings rooted in tubes.